Pengaruh Leverage Ratio, Capital Structure, Dan Sales Growth Terhadap Financial Distress : (Studi Kasus Pada Perusahaan Startup Sektor Teknologi yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2022-2024) - I Gusti Ayu Agung Pradnya Pramesty; Ni Komang Sumadi; Ni Ketut Muliati (UNHI Press, 2026)
This study aims to examine the effect of leverage ratio, capital structure, and sales growth on financial distress in technology sector startup companies listed on the Indonesia Stock Exchange (IDX) for the period 2022-2024. The population of this study comprises all technology sector startup companies listed on the Indonesia Stock Exchange (IDX) for the period 2022-2024, totaling 13 companies. The sampling technique used is saturated sampling (census method), which is a sample determination method where all members of the population are used as samples, resulting in a total sample of 39. To test the hypotheses, descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, coefficient of determination test, F-test, and t-test were conducted with the assistance of SPSS. The results of the study indicate that the leverage ratio (DAR) has a positive effect on financial distress, capital structure (DER) has a positive effect on financial distress, and sales growth has a negative effect on financial distress.